PENGARUH LATIHAN TENDANGAN KE ATAS KURSI TERHADAP KETERAMPILAN TENDANGAN DEPAN PADA EKSTRAKURIKULER PENCAK SILAT DI SMK BINA INSAN MANDIRI (Universitas Majalengka, 2021)
ABSTRACT. This study based on students whose be a part of pencak silat extracurricular that during the front kick technique uncorrectly. due to question of consider, is there an effect of kick training on a chair on front kick skills in pencak silat extracurricular at SMK Bina Insan Mandiri?And the purpose of the study was to determine the effect of kick training on a chair on front kick skills in pencak silat extracurricular at SMK Bina Insan Mandiri. The research method used was experimental with Pre-Experimental Design in the form of one group pretest posttest. The population and sample are students who take extracurricular pencak silat at SMK Bina Insani, totaling 16 people taken by total sampling. this test of study used was a kick skill test that was adapted from Lubis and Wardoyo. Data analyse of using paired sample t test Based on process this data show us there was an increase of 4.125, with a standard deviation of 0.719. Sig value (2-tailed) obtained a value of 0.000. that can be conclude, the sig value is smaller than the alpha value (0.000 < 0.05). So it can be concluded that there is an effect of kick training on a chair on front kick skills in extracurricular pencak silat at SMK Bina Insan Mandiri. The researcher recommends the up-chair kick basic exercise as an alternative to train and improve the front kick technique. Keywords: The Front kick, chair as obstacle, and effective efficient